RELATIONSHIP OF BODY INDEX (BMI) WITH PRAMENSTRUATED SYNDROME IN NURSING STUDENT PROGRAMS AT THE UNIVERSITY OF BHAKTI KENCANA TASIKMALAYA - Meti Sulastri; Lina Marlina; Iis Sopiah Suryani (SEKOLAH TINGGI ILMU KESEHATAN (STIKes) INDRAMAYU, 2020)
Premenstrual syndrome is a collection of the physical, psychological and emotional symptoms associated with the menstrual cycle. About 80 to 95% of women experience premenstrual symptoms that can interfere with their activities. Some of the factors that can cause premenstrual syndrome are increased levels of the hormone estrogen. The basic ingredient of estrogen is fat, to be able to predict fat in the body by measuring the body mass index. The research design used analytic observational. The purpose of this study was to analyze the relationship between body mass index and premenstrual syndrome in undergraduate nursing study program students. The sample in this study using random sampling of 63 respondents. The results showed that the highest index of body mass in the thin category was 24 people (38.1%) and the incidence of premenstrual syndrome showed that the highest frequency was not experiencing premenstrual syndrome, namely 37 people (56.7%), while the bivariate analysis showed that there was a significant relationship between the indices. Body mass with premenstrual syndrome in undergraduate nursing study program students with a p-value = 0.031. Respondents are expected to be able to take better precautions and carry out their daily routine to run premenstrual syndrome.